On the nature of botanical gardens; Decolonial aesthesis in Indonesian contemporary art - Boonstra, Sadiah (UI Scholars Hub, 2022)
This article examines decolonial approaches to the nature of botanical gardens in Indonesia in the artworks of nine artists featured in the exhibition On the nature of botanical gardens: contemporary Indonesian perspective at Framer Framed, Amsterdam in 2020. Zico Albaiquini, Arahmaiani, Ade Darmawan, Edwin, Samuel Indratma, Lifepatch, Ipeh Nur, Elia Nurvista, and Sinta Tantra presented works which confronted the coloniality of botanical gardens. This article provides a historical reading of the content matter of the artworks presented from a decolonial standpoint as conceptualized by Aníbal Quijano, Walter Mignolo, and María Lugones. The article will demonstrate that the artists have applied various strategies and methods to uncover, criticize, and decolonize botanical gardens and their role in empire-building, knowledge development, and the exploitation of nature. Some artists take this farther and develop a decolonial aesthesis or sensibility in order to re-appropriate Indigenous knowledges and ways of being which were silenced and erased by coloniality.